Soft Interaction in Liposome Nanocarriers for Therapeutic Drug Delivery - Domenico Lombardo (Nanomaterials, 2016)
The development of smart nanocarriers for the delivery of therapeutic drugs has experienced considerable expansion in recent decades, with the development of new medicines devoted to cancer treatment. In this respect a wide range of strategies can be developed by employing liposome nanocarriers with desired physico-chemical properties that, by exploiting a combination of a number of suitable soft interactions, can facilitate the transit through the biological barriers from the point of administration up to the site of drug action. As a result, the materials engineer has generated through the bottom up approach a variety of supramolecular nanocarriers for the encapsulation and controlled delivery of therapeutics which have revealed beneficial developments for stabilizing drug compounds, overcoming impediments to cellular and tissue uptake, and improving biodistribution of therapeutic compounds to target sites. Herein we present recent advances in liposome drug delivery by analyzing the main structural features of liposome nanocarriers which strongly influence their interaction in solution. More specifically, we will focus on the analysis of the relevant soft interactions involved in drug delivery processes which are responsible of main behaviour of soft nanocarriers in complex physiological fluids. Investigation of the interaction between liposomes at the molecular level can be considered an important platform for the modeling of the molecular recognition processes occurring between cells. Some relevant strategies to overcome the biological barriers during the drug delivery of the nanocarriers are presented which outline the main structure-properties relationships as well as their advantages (and drawbacks) in therapeutic and biomedical applications.